Titan's atmosphere simulation experiment using continuum UV‐VUV synchrotron radiation. Issue 4 (17th April 2013) - Peng, Z.; Gautier, T.; Carrasco, N.; Pernot, P.; Giuliani, A.; Mahjoub, A.; Correia, J.‐J.; Buch, A.; Bénilan, Y.; Szopa, C.; Cernogora, G.
Abstract : [1] A new reactor, named APSIS for Atmospheric Photochemistry Simulated by Synchrotron, is designed for simulating the reactivity occurring in planetary upper atmospheres. In this reactor, a gas mixture roughly reproducing Titan's main atmosphere composition (N2 /CH4 = 90/10) is irradiated by a continuous spectrum in the 60−350 nm range, provided by the DISCO beamline at the SOLEIL synchrotron radiation facility. This spectral range enables the dissociation and ionization of N2 and CH4, as observed in plasma reactors and Titan's ionosphere. The neutral products are detected in situ by quadrupole mass spectrometry and collected with a cryogenic trap for ex situ analysis by gas chromatography‐mass spectrometry. The detected reaction products include C2, C3, C4, and probably C5 organic compounds, with important amounts of nitrogen‐bearing species: HCN, CH3 CN, and C2 N2 . Neutral mass spectra obtained with APSIS are compared with Ion and Neutral Mass Spectrometer experiments of the Cassini space probe in the upper Titan atmosphere and with other results of current Titan atmosphere chemistry laboratory simulations. Key Points: APSIS is a new reactor to study reactivity in planetary ionospheres Windowless operation enables VUV irradiations below Lyman‐alpha APSIS opens new pathways for simulating planetary ionospheric chemistry